Experimental study of operating parameters in zero-gap CO2 electrolysis - Zhong, Siyu; Ait Aissa, Ilyes; Huang, Gen; Holtappels, Peter; Liu, Sijia; Dittmeyer, Roland (Frontiers in Catalysis, 2025)
Electrochemical CO2 reduction represents a promising approach for mitigating carbon emissions while generating value-added fuels and chemicals. While catalyst design mainly dictates activity and product selectivity, system-level performance is strongly influenced by the interplay between electrolyzer configuration and operating parameters. In this study, a zero-gap membrane electrode assembly electrolyzer incorporating a cation exchange membrane is systematically investigated under practical considerations. The applicable operating window is successfully extended to elevated temperatures and pressures, demonstrating robust practicality and efficient conversion. Comprehensive evaluation of cell voltage, Faradaic efficiency, and energy efficiency reveals that a balanced combination of catalyst loading, electrolyte concentration, and flow rate enables high CO selectivity (>90%) and energy efficiency exceeding 40% at moderate current density (100 mA/cm2). By integrating multiple operational parameters, this work advances the application of cation exchange membrane based CO2 electrolysis and offers practical insights for bridging laboratory research and scalable implementation.